Survey appropriate amount of MRI services provided in Shahid Chamran hospital of Shiraz - abozar sadeghi; khosro keshavarz; mahdiye sadat ahmadzadeh; alireza (Mazandaran University of Medical Sciences, 2015)
Background: According the importance of MRI in the treatment process and the high cost of buying and maintaining it for centers and high cost for patients, this study aimed to determine the appropriate Services MRI provided in a hospital in Shiraz and the cost of per serving that are inappropriate to use the data for reduce unnecessary Prescription MRI. Methods: This cross-sectional study is done in March 2015 at a hospital in Shiraz University of Medical Sciences. To collect information. all services performed Divided by region and type of MRI were extracted from HIS system. In this study,  was evaluated. To estimate the cost of unnecessary items used the Vice Chancellery of clinical affairs report in 2013. The data were analyzed using in spss software. Results: The results showed that during this period of time, 2105 number of people used of this Services. that 517 patients (24%) as a result of normal, and 1588 patients (76%)  were abnormal. The cost of the unnecessary items was estimated at 609180000 riyals. Conclusion: Due to the catastrophic costs of the service, which was entered on the patient and the insurance can be Identify affecting factors in use of these services, in order to receive to better use and avoid the increasing use of this service. Keywords: Diagnostic services, MRI unnecessary, Imaging, Hospital